Bromocriptine Use in Peripartum Cardiomyopathy: Review of Cases - Simon, Rebecca; Yang, Sophia; Hameed, Afshan B. (American Journal of Perinatology Reports, 2018)
Objective This study is to review published cases of peripartum cardiomyopathy (PPCM) treated with bromocriptine and outline pros and cons of the treatment strategy.Data Sources Data were collected from PubMed/MedLine, ClinicalTrials.gov; the years 2007 to 2018 were searched for English-language articles. Search terms: “bromocriptine and peripartum cardiomyopathy”, “bromocriptine and cardiomyopathy.”Methods of Study Selection This search strategy yielded 171 articles. After excluding duplicates, 86 studies were reviewed. Sixty-one articles involving the treatment of PPCMP were included, and of these, 17 were case reports of patients with PPCMP treated with bromocriptine; these studies were included in this review.Tabulation, Integration, and Results Seventeen of these articles were case reports of patients with peripartum cardiomyopathy treated with bromocriptine that were included.Conclusion Bromocriptine seems to be a promising treatment, there is currently insufficient evidence for universal utilization of bromocriptine for all patients with PPCMP. Addition of bromocriptine to the standard heart failure therapy should be individualized.
Keywords: peripartum cardiomyopthaty; bromocriptine; left ventricular function; recovery; pregnancy; right ventricular function